A probabilistic quantum key transfer protocol. Issue 11 (13th March 2013) - Parakh, Abhishek
ABSTRACT: We propose a protocol to transfer a one‐time pad (in a probabilistic manner) from Alice to Bob, over a public channel. The proposed protocol is unique because Bob merely acts as a receiver of the pad (secret key); that is, Bob does not need to send any message back to Alice unless he detects eavesdropping. Such a secure transfer of one‐time pad, over public channel, is not possible in classical cryptography, and in quantum cryptography, all previous protocols require Bob to send almost as many messages back to Alice as she does to Bob to establish a key. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : We propose a protocol to transfer a one‐time‐pad (in a probabilistic manner) from Alice to Bob, over a public channel. The proposed protocol is unique because Bob merely acts as a receiver of the pad. Such a secure transfer of one‐time‐pad, over public channel, is not possible in classical cryptography and in quantum cryptography all previous protocols require Bob to send almost as many messages back to Alice as she does to Bob, to establish a key.